Konsep A‘addah dalam pengurusan pindahmilik harta pusaka / Roshaimizam Suhaimi and Jasni Sulong - Suhaimi, Roshaimizam; Sulong, Jasni (Universiti Teknologi MARA, Pulau Pinang, 2014)
The word a‘addah or"preparation" is mentioned 14 times in the Quran which shows the importance of preparation in Islam. Through proper preparation and planning, the effort can run smoothly and the ultimate goals can be achieved in time. It is a step to be taken before starting a task in preventing failure or work difficulties. In this study, the focus of preparation is in the administration of estate; to ensure the smooth and fair process of transferring the wealth to all the right heirs. In addition, through early preparation, an owner of the estate is able to identify the legal heir. The benefit and welfare of the heirs who are legally deprived from inheriting the wealth can also be guaranteed by other methods of transfer such as by will or gift. Preparation also ensures that the rights of other beneficiaries such as creditor, leaser and tenant are taken care of. In this study, a qualitative research method was adopted to examine the concept of Islamic law in regards to preparation and its application in the statutes, particularly in the administration of inheritance. The findings showed that the preparation process of distributing inheritance becomes smoother and less complicated. Besides, it also develops an alternative distribution method to guarantee the welfare of the dependants as a symbol of continuous support from the family.